The Power of Positive Thinking - Peale, Norman Vincent, 1898-1993 (Kingswood The World's Work (1913) Ltd., 1958)
Dr. Peale shares his formula for positive thinking and success in this 35th commemorative edition
Keywords: Peace of mind--Religious aspects--Christianity -- Success--Religious aspects--Christianity